ANALISIS STRATEGI PEMBIAYAAN ( FINANCE ) DALAM UPAYA MEREBUT PANGSA - Heriyanto, Aidina Maretsya, H. Eddy Soegiarto K (EKONOMIA, 2015)
The purpose of this paper to determine the internal aspects of the company's strengths and weaknesses and the opportunities and threats of the external aspects of the company to formulate appropriate strategies as a benchmark in formulating the company's strategy to increase its profits. Formulation of the problem in this paper is, Where is the position of the company in carrying out its activities on the SWOT analysis (Strength, Weakness, Opportunitiess and Threats)? The hypothesis of this study is the position of the company is located in the first quadrant on the SWOT matrix in which the company is very profitable situation. The company has the opportunity and the power that can take advantage of existing opportunities and the company's position, strategies appropriate in these circumstances is to support aggressive growth policy (Growth-oriented strategy) that uses all the power to seize and exploit opportunities as possible.                From the research results can be seen in the total score calculation result of internal factors to aspects of the power of 2.082 and weaknesses aspects of (1.222), the difference in value of 0.86 is describe as the organization's position on aspects of the strengths and weaknesses aspects. While the results of the calculation of the external factor scores for aspects of 2.025 opportunities and challenges aspects of (1.195), the difference in value of 0.83 is describe as the organization's position on aspects related aspects of the opportunities and challenges. Based on calculations were greatest in the first quadrant, the research hypothesis is accepted.